Transtornos mentais comuns nos alunos do curso de medicina de uma Universidade Federal: compreensões a partir da socionomia. - Nepomuceno, Wellyka de Araújo Pinto (2021)
In the current scenario, it is clear that a high number of medical students face some form of psychological distress. Research indicates that the rates of Common Mental Disorders (CMD) in medical students tend to be above average when compared with general population. Among the possible causes are: high hours of activities, overload of knowledge, difficulties with time management, as well as few opportunities for leisure and rest. With this work, the objective is to understand CMD in students of the Universidade Federal do Ceará. For this to be possible, it is a mixed research in which, initially, the Self-Reporting Questionnaire (SRQ-20) will be applied to 278 enrolled in the Medical Course, in the semester of 2020.1, in order to investigate the cases of students with indications of Common Mental Disorders (CMD). Together with this data collection instrument, a sociopsychodemographic questionnaire will be applied. The results of this first phase, the quantitative phase, will serve as a basis for the qualitative phase, in which thematic sociodrama sessions will be applied with some of theses students, as it is understood that through this technique one can have a new understanding about CMD. Studies point out that, in addition to being a methodological research tool, sociodrama also works as an instrument of intervention in the environment, thus, it is hoped that, at the end of this research, the data obtained can serve as a basis for investing in a pertinent psychological support service for medical students and that the sociodrama sessions have been successful, for example, in resolving conflicts and generating reflections on new ways of understanding CMD.